Sputtered Titanium Carbide Thick Film for High Areal Energy on Chip Carbon‐Based Micro‐Supercapacitors. (31st March 2017) - Létiche, Manon; Brousse, Kevin; Demortière, Arnaud; Huang, Peihua; Daffos, Barbara; Pinaud, Sébastien; Respaud, Marc; Chaudret, Bruno; Roussel, Pascal; Buchaillot, Lionel; Taberna, Pierre Louis; Simon, Patrice; et al.
Abstract : The areal energy density of on‐chip micro‐supercapacitors should be improved in order to obtain autonomous smart miniaturized sensors. To reach this goal, high surface capacitance electrode (>100 mF cm −2 ) has to be produced while keeping low the footprint area. For carbide‐derived carbon (CDC) micro‐supercapacitors, the properties of the metal carbide precursor have to be fine‐tuned to fabricate thick electrodes. The ad‐atoms diffusion process and atomic peening effect occurring during the titanium carbide sputtering process are shown to be the key parameters to produce low stress, highly conductive, and thick TiC films. The sputtered TiC at 10 −3 mbar exhibits a high stress level, limiting the thickness of the TiC‐CDC electrode to 1.5 µm with an areal capacitance that is less than 55 mF cm −2 in aqueous electrolyte. The pressure increase up to 10 −2 mbar induces a clear reduction of the stress level while the layer thickness increases without any degradation of the TiC electronic conductivity. The volumetric capacitance of the TiC‐CDC electrodes is equal to 350 F cm −3 regardless of the level of pressure. High values of areal capacitance (>100 mF cm −2 ) are achieved, whereas the TiC layer is relatively thick, which paves the way toward high‐performance micro‐supercapacitors. Abstract : High areal capacitance carbide derived carbon (CDC) electrodes are produced from sputtered thick titanium carbide (TiC) . The stress level is carefully controlled to deposit a thick TiC layer. Moving from 10 −3 up to 10 −2 mbar allows for reduction of the atomic peening effect responsible for the TiC densification and to produce TiC‐CDC electrodes reaching up to 100 mF cm −2 areal capacitance in aqueous electrolyte while keeping constant the electronic conductivity.